2021
DOI: 10.3233/jad-210008
|View full text |Cite
|
Sign up to set email alerts
|

Is the Frontal Lobe the Primary Target of SARS-CoV-2?

Abstract: Acute delirium and other neuropsychiatric symptoms have frequently been reported in COVID-19 patients and are variably referred to as acute encephalopathy, COVID-19 encephalopathy, SARS-CoV-2 encephalitis, or steroid-responsive encephalitis. COVID-19 specific biomarkers of cognitive impairment are currently lacking, but there is some evidence that SARS-CoV-2 could preferentially and directly target the frontal lobes, as suggested by behavioral and dysexecutive symptoms, fronto-temporal hypoperfusion on MRI, EE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
45
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 36 publications
3
45
1
3
Order By: Relevance
“…Accordingly, isolated frontocingulate dysfunction among COVID-19 survivors may underlie deficits in executive function while other cognitive processes remain unscathed. Some postulate that frontal circuitry is preferentially targeted by SARS-CoV-2, contributing to executive dysfunction ( Toniolo et al, 2021 ). Direct links between frontal lobe abnormalities and cognitive impairment post-COVID-19 are lacking, but there is some evidence of frontal hypometabolism in severe cases ( Hosp et al, 2021 ; Matschke et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, isolated frontocingulate dysfunction among COVID-19 survivors may underlie deficits in executive function while other cognitive processes remain unscathed. Some postulate that frontal circuitry is preferentially targeted by SARS-CoV-2, contributing to executive dysfunction ( Toniolo et al, 2021 ). Direct links between frontal lobe abnormalities and cognitive impairment post-COVID-19 are lacking, but there is some evidence of frontal hypometabolism in severe cases ( Hosp et al, 2021 ; Matschke et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Five were diagnosed with mild COVID-19, and two had a moderate disease based primarily on the presence or absence of symptoms of mild pneumonia. Neurologic symptoms developed at a median of 16 (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33) days after initial COVID-19 manifestations. All patients had headache and altered behavior (reported as mild irritability 1 lists the laboratory test results.…”
Section: Resultsmentioning
confidence: 99%
“…Considering our patients' impairments in verbal fluency, poor constructional strategies, and behavior alterations, the dorsolateral prefrontal circuit, the anterior cingulate cortex, and the lateral orbitofrontal circuit are likely the most affected regions in SARS-CoV-2 encephalopathy. These circuits have been associated with different types of subcortical infectious dementia and hypothesized as affected in COVID-19 ( 32 , 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…Supporting the CSN tropism of the virus, several studies have indicated the SARS-CoV-2 presence in the brain of patients affected by epilepsy [ 11 ], cerebral edema [ 12 ], encephalitis [ 13 ], and multiple sclerosis [ 14 ]. Recent hypothesis suggest that the frontal lobes in particular could be a specific target of SARS-CoV-2 infection [ 15 ].…”
Section: Introductionmentioning
confidence: 99%